Digital Marketing in Promoting Tourism and Other Services - Pavlovska, Iryna; Stamat, Viktoriia; Sogorin, Andriy; Voskresenska, Olena; Shepeleva, Olga (International Review of Management and Marketing, 2026)
The offered relevance structure is based on the rise of digital technologies in tourism and similar service industries where digital marketing determines demand development and competitive position of actors. The quick engagement of these digital tools in services advertising methodology brings forth naïve stereotypes and not any systematic intricate or quantitative study for long-term trend estimation. This highlights the need for a more in-depth understanding of digital behaviours and engagement patterns, use and effectiveness of digital marketing communications through internationally comparative data. The goal of the study is to reveal and measure development dynamics in application of digital marketing tools, activeness of consumers, and efficiency of digital-marketing communication (for tourism related service) based on international data during 2020–2024; the object is processes for digital marketing communication in service organizations. Methodological the research includes empirical quantitative analysis, descriptive methods, and comprehensive statistics for secondary and international comparative data during 2020–2024. It was concluded that the intensity of use of DM tools in tourism and related industries is increasing. Digital channels show stable growth, reaching a more even level after 2022. Consumer involvement analysis shows increased time devoted to digital content and online communication. Findings indicate greater exposure to digital marketing communications and engagement. Scientific novelty consists in the possibility to use established patterns for forming strategic directions for long-term development of tourism and service companies, including digital marketing.